A dissociation mechanism for the [a plus c] dislocation in GaN - Nellist, P; Hirsch, P; Rhode, S; Horton, M; Lozano, J; Yasuhara, A; Okunishi, E; Zhang, S; Sahonta, S; Kappers, M; Humphreys, C; Moram, M (Institute of Physics Publishing, 2014)
Mixed-type [a+c] dislocations can be identified in atomic-resolution high-angle annular dark-field scanning transmission electron microscope images of GaN viewed along [0001] by use of a Burgers loop analysis and by observation of the depth-dependent displacements associated with the Eshelby twist. These dislocations are found to be able to dissociate resulting in a fault that lies perpendicular to the dislocation glide plane. Consideration of the bonding that occurs in such a fault allows the dissociation reaction to be proposed, and the proposed fault agrees with the experimental images when kinks are incorporated into the model. © Published under licence by IOP Publishing Ltd.